(untitled) (Education in the 21st Century, 2023)
Problem-Based Learning is a technology for the development of students, the formation of their beliefs, the application of what has been learned in practice, which is used when problematic situations arise in the teaching process and raises problematic questions. This teaching technology, answering the raised problematic questions, activates the cognitive activity of students, develops thinking and allows replenishing the luggage of the student’s knowledge. The application of the Problem-Based Learning technology in the university course supposes the preparatory work. First of all, it is necessary to study the teaching material of the entire topic and each lesson separately, highlight the main ideas and formulate the learning goal for students in order to show that at the end of the lesson the student should learn, know, be able to understand and determine what other skills should be acquired. Secondly, it is necessary to choose additional materials for students (for example, books, various Internet resources), as well as to give them different assignments and test-works. Depending on the volume of the educational material, the work organized in accordance with the technology of Problem-Based Learning may include the whole lesson or a part of it. The Problem-Based Learning technology provides individualization in terms of learning, speed of apprehension, the level of independence, teaching methods, the methods of control and self-control. It foresees the creation of positive motivations of teaching due to the novelty of the content, the appearance of emotional content, the organization of educational researches and overcoming of cognitive difficulties. In the university course of the Armenian language, the application of the Problem-Based Learning technology is effective, especially when teaching grammar, in particular, when studying the semantic and applied features of parts of speech, grammatical categories, verb affixes, aspect and tense forms of the verb, through the combination of problematic teaching techniques with interactive methods.